RETRACTED: Recycling in Textile Sector: A New Circular Economy Approach Towards Ecology and Environmental Sustainability - Liu, Xiaolian; Wang, Shuangao; Li, Yuhong; Ali, Shamsher; Khan, Yousaf Ali; Salem, Sultan; Huang, Xiaobing (Frontiers in Environmental Science, 2022)
Sustainable supply chain management techniques have been developed over the last several decades to reduce accidental environmental damage during production and buying. Ensuring a practical connection between ecosystems and economic development, Circular economies push the limits of environmental sustainability. There are two types of rebound effects in the studied business. The impacts of circular business models and strategies are examined and put in a broader framework to get a better understanding of their role in the transition. In order to put transitory changes in a system perspective, this calls for a new approach to design. Rebound effects and designing an eco-effective transition are discussed as theory-building elements. We conclude by suggesting several future research directions.